Communicating bad news: an integrative review of the nursing literature - Bertoncello Fontes, Cassiana Mendes [UNESP]; Menezes, Daniele Vieira de; Borgato, Maria Helena [UNESP]; Luiz, Marcos Roberto [UNESP] (Assoc Brasileira Enfermagem, 2017)
Objectives: describe how the process of breaking bad news is established and identify how nurses approach the task of giving bad news. Method: integrative review of the literature for articles in Portuguese and English published between 1993-2014, in the databases: Bireme, PubMed, Scopus, Web of Science, CINAHL and Embase. Nine articles were included using the selection flow chart. A digital form was completed for each article according to the Consolidated Criteria for Reporting Qualitative Research checklist and the level of scientific evidence was determined. Results: Of the 99 articles in identified, nine were included after applying the selection flowchart. Discussion: breaking bad news is frequent in the area of oncology and palliative care, with a strong cultural influence on the autonomy of nurses in this process. Conclusion: the approach and skills of the nurse during this task influences the patient's reaction to the message. The theme is scarce in the literature and merits further investigation.
Keywords: Truth-Telling; Communication; Nursing; Family; Information